WTO in the Arena of the Indonesian Industrial Revolution 4.0: A Strategy to Improve the Quality of Indonesian Human Resources Through International Trade - Tiara Almira Raila; Jeremias Palito (LEGAL BRIEF, 2020)
The industrial revolution is a necessity. The real obstacle faced by Indonesia as a developing country in entering the industrial revolution 4.0 is the problem of the quality of human resources (HR), energy, infrastructure which includes transportation, facilities and infrastructure, technology and information. Therefore, as a form of commitment to the industrial revolution 4.0, Indonesia as a country and the WTO as an international organization must truly implement an optimal trade and development mechanism for the creation of a healthy climate of economic globalization. In addition to support through the economic strategy in the industrial revolution 4.0, the WTO is also committed to improve the quality of HR in its member countries. Improving the quality of human resources in the industrial Revolution 4.0 is crucial. In Indonesia, a link and match program between the education sector and the industrial sector have helped a lot in increasing the quality of human resources.